Definition and validation of Eurocode 3 FAT classes for structural steels containing oxy-fuel, plasma and laser cut holes. (June 2016) - Cicero, S.; García, T.; Álvarez, J.A.; Martín-Meizoso, A.; Aldazabal, J.; Bannister, A.; Klimpel, A.
Highlights: Eurocode 3 only considers the fatigue performance of drilled holes. This paper studies the fatigue performance of oxy-fuel, plasma and laser cut holes. An experimental program composed of 150 fatigue specimens has been completed. Eurocode 3 FAT classes have been derived and validated. Abstract: When the fatigue behaviour of structural components containing holes is analysed, Eurocode 3 only considers the fatigue performance of drilled holes, limiting the use of thermal cutting processes to produce, for example, bolt holes. This paper studies the fatigue performance of structural steel plates containing thermally cut holes. The research covers three thermal cutting methods: the traditional one (oxy-fuel cutting) and two more modern processes (plasma and laser cutting). An experimental program composed of 150 fatigue specimens has been completed, combining four steels (S355M, S460M, S690Q and S890Q), the three thermal cutting methods and two different thicknesses (15 mm and 25 mm). The S–N results obtained have been used to estimate the corresponding Eurocode 3 FAT classes, which have finally been validated by comparing them to additional experimental data found in the literature.